The Effect of Accountability and Auditor Independence on Internal Audit Quality (Study on the Inspectorate of West Bandung Regency) - Ari Bramasto (SEAN Institute, 2024)
This research is a quantitative study, which aims to determine: 1) the influence of accountability on the quality of internal audit, 2) the influence of auditor independence on audit quality. internal, and 3) the influence of accountability and independence on the quality of internal audit. The sampling technique used is saturated sampling technique or census, all members of the population are sampled so that there are 45 respondents. The tests carried out in this study include descriptive statistics, validity tests, reliability tests, classical assumption tests (normality test, heteroscedasticity test and, multicollinearity test), multiple linear regression, correlation coefficient test, coefficient of determination test, t test, and f test which processed using SPSS (Statistical Product and Service Solutions) software for Windows version 26. The results of this study show that 1) there is an influence of accountability on the quality of internal audits. 2) there is an influence of auditor independence on the quality of internal audits. 3) there is an influence of accountability and independence of auditors on the quality of internal audits.